Contribución a la tipobibliografía vallisoletana (1600-1672): seis impresos relacionados con Galicia - Santos Fernández, Carlos (Revista General de Información y Documentación, 2007)
Description of six documents printed in Valladolid and related to Galicia: three privileges granted by Felipe III, corresponding to three rights of perpetual ownership of you inheritance bought by the Church of Santiago de Compostela (Juan de Bostillo, 1600), one bull of the Monastery of Santo Toribio de Liébana (Laurencio de Ayala, 1602) which was reproduced fakely in Santiago by the typographer Juan Pacheco who was eventually taken to jail, a notification of the change of the celebration of Santa Teresa de Jesús (Viuda of Francisco de Córdoba, 1629) who favored the interests of the teresiano copa- tronage against the patronage of Santiago and a hornbook for the prayer of the saints in the compostelan’s diocese for the year 1672 (Juan Antolín de Lago, 1671).